Evaluasi Ketepatan Pengelolaan Diskon & Promo Dalam Laporan Keuangan Pada Alfamidi - Hamid Rinaldo Zebua; Dedi Irawan Zebua; Serniati Zebua; Kurniawan Sarototonafo Zai (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
In the modern retail industry, discounts and promotions at Alfamidi aim to increase sales and customer loyalty. However, improper recording can affect revenue, profit and loss, and marketing expenses. Discrepancies were found between shelf prices and cashier (POS) system prices, as well as weaknesses in internal control. An evaluation is therefore necessary to ensure that promotional management complies with Financial Accounting Standards (SAK), remains accurate, and does not cause distortions in financial statements or financial losses for the company.This research uses a qualitative method to gain an in-depth understanding of discount and promotion management at Alfamidi. The study was conducted at the store located on Jalan Diponegoro No. 03, Gunungsitoli, with primary data obtained through interviews and observations. The analysis was carried out using a descriptive qualitative approach through data reduction, data presentation, and conclusion drawing to ensure validity and to describe the structure of financial statement recording.The results show that discount and promotion management follows structured procedures, starting from marketing proposals, financial verification, to implementation in accordance with standard operating procedures (SOP). The recording refers to PSAK 23 and PSAK 1 issued by the Ikatan Akuntan Indonesia, supported by proper documentation and an ERP system. Challenges include delays in data input and differences in perception regarding classification. Daily monitoring, internal audits, data reconciliation, and ERP utilization serve as solutions to improve the accuracy and transparency of financial statements.The conclusion indicates that Alfamidi has structured procedures for discounts and promotions, with recording practices aligned with PSAK 23 and PSAK 1, although technical and coordination challenges remain. Improvements are needed through stronger internal controls and training. Future research is suggested to expand resources, deepen documentation analysis, identify constraints in greater detail, apply mixed methods, and broaden research objects to obtain more comprehensive and valid results.